Menjembatani Turats dan Modernitas: Analisis Komparatif-Kritik Hermeneutika Abdullah Saeed dan Mahmoud Ayoub - Mohammad Maulana Khoirur Rifki; Rida Fahimatul Aaliyah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study examines the contemporary hermeneutical approaches of Abdullah Saeed and Mahmoud Ayoub as significant contributions to bridging the intellectual gap between Islamic classical tradition (turats) and modern socio-cultural realities. Employing a qualitative library research method, the analysis focuses on Saeed’s contextualist framework, which emphasizes the hierarchy of ethico-legal values and the evolution of Qur’anic meaning across time, and Ayoub’s historical-integrative method, which revitalizes the rich plurality of classical exegesis while maintaining continuity with the living tradition of Islamic scholarship. The study reveals that Saeed’s approach is future-oriented, aiming to reinterpret Qur’anic teachings to address human rights, gender equality, and social justice in contemporary contexts. Conversely, Ayoub’s approach is reconstructive, highlighting intertextual dialogue within classical tafsir to preserve the Qur’an’s spiritual and intellectual depth across generations. By comparing these methodologies, the research demonstrates that both scholars challenge absolutist claims of interpretation and promote a dynamic understanding of revelation. The study concludes that their hermeneutical contributions provide a constructive pathway for Qur’anic interpretation that is both faithful to tradition and responsive to modern realities.